Apoptotic induction in CCRF-CEM and HL-60 human leukemic cell lines by 5-Azacitidine and trichostatin A. - Aziee, Sudin; Haiyuni, Mohd Yassim; Nagi Al-Jamal, Hamid Ali; Shafini, Mohamed Yusoff; Abdul Wahab, Ridhwan; Shamsuddin, Shaharum; Johan, Muhammad Farid (Advanced Medical and Dental Institute (AMDI), Universiti Sains Malaysia., 2018)
The aims of the study were to investigate the anti-cancer effects of 5Aza and TSA in two leukemic cell lines (CCRF-CEM and HL-60). Inhibition concentration of 5-Aza and TSA were measured using trypan blue exclusion assay. 5-Aza and TSA at IC50 were treated to both CCRF-CEM and HL-60 cell lines for 4-6 days. To confirm the inhibition effects of these agents, Annexin-V stained cells were analyzed using flow cytometry to evaluate the apoptotic induction. The IC50 values of CCRF-CEM were 2.01±0.1µM and 2.65±0.3µM for 5-Aza- and TSA-treated, respectively. Whereas, the IC50 values of HL-60 were 1.98±0.2µM and 2.35±0.2µM for 5-Aza- and TSA-treated, respectively. To further substantiate the findings, the time-dependent exposure of both drugs was studied. CCRF-CEM cells were reduced to 49.4%±5.0, 49.4%±2.5 and 41.5%±5.6 by 5-Aza; 56.5%±7.0, 45.3%±4.2 and 40.2%±4.2 by TSA treatment at first, third and sixth day. HL-60 cells were reduced to 72.0%±4.5, 51.0%±1.5 and 40.6%±2.6 by 5-Aza at first, third and sixth day. Meanwhile, HL-60 cells reduced to 55.6%±4.5, 45.2%±4.0 and 36.3%±2.9 by TSA at first, second and fourth day. Both cell lines were significantly inhibited (p<0.05) compared to the untreated. Furthermore, flow cytometry demonstrated that 5-Aza and TSA significantly increased the cells population positive for Annexin-V in CCRF-CEM and HL-60 cell lines. In CCRF-CEM, the total apoptotic rates were 51.7%±9.7 and 49.4%±6.0 for 5-Aza- and TSA-treated, while, in HL-60, the apoptotic rates were 51.0%±3.9 and 49.7%±9.6 for 5-Aza- and TSA-treated, in a dose- and time-dependent manner, respectively. Epigenetic modification drugs, 5-Aza and TSA have anti-leukemic effects and induce apoptosis at micro-molar concentrations in CCRF-CEM and HL-60 leukemic cell lines. These results may provide a new insight into the use of 5-Aza and TSA in inhibiting the growth of leukemic cells and useful strategy in developing an epigenetic therapy.